Analisis Taburan Warga Emas dan Etnik di Sarawak : Tinjauan Empat Dekad [1980-2020] (Analysis of The Distribution of Senior Citizens and Ethnic Groups in Sarawak: A Review of Four Decades [1980-2020]) - Asykal Syakinah, Mohd Ali; Tarmiji, Masron; Syahrul Nizam, Junaini; Luqman Haqim, Bismelah; Azizul, Ahmad (International Journal of Children, Women, The Elderly and Persons with Disabilities (IJCWED eISSN 0128-309X), 2025)
The increase in the senior citizen population worldwide has led to significant demographic changes, which have become a primary concern as they affect various aspects such as healthcare systems, social welfare, and the labor market. However, there is a gap in the literature regarding how this trend affects population distribution at the regional level, particularly in Sarawak. Therefore, this study aims to discuss the distribution of the population aged 65 and above in Sarawak from 1980 to 2020 and analyze the relationship between the senior citizens population and ethnic groups in Sarawak. Data on elderly people from 1980 to 2020 were used in this study, and descriptive analysis was conducted based on regions in Sarawak. The initial findings indicate a significant growth in the number of elderly individuals in certain areas, which may impact the need for services and infrastructure for the elderly population. Additionally, the analysis of the relationship between the senior citizens population and ethnic groups provides new insights into the social and cultural dynamics in Sarawak. These findings are expected to guide the development of policies and programs aimed at improving the well-being and social welfare of the elderly population.